Amaranthus palmeri “Palmer amaranth” - Sergio Morichetti; Jason Ferrell (EDIS)
SS-AGR-336, a 5-page illustrated fact sheet by Sergio Morichetti and Jason Ferrell, demonstrates how to accurately identify this fast growing, herbicide resistant weed in the “pigweed” group, so that it can be properly managed before the population grows to such a degree that effective control becomes impossible or prohibitively expensive. Published by the UF Department of Agronomy, August 2010.